2015
DOI: 10.3171/2014.10.jns14963
|View full text |Cite
|
Sign up to set email alerts
|

Microrecording and image-guided stereotactic biopsy of deep-seated brain tumors

Abstract: OBJECT Image-guided stereotactic brain tumor biopsy cannot easily obtain samples of small deep-seated tumor or selectively sample the most viable region of malignant tumor. Image-guided stereotactic biopsy in combination with depth microrecording was evaluated to solve such problems. METHODS Operative records, MRI findings, and pathological specimens were evaluated in 12 patients with small deep-seated brain tumor, in which image-guided stereotactic biopsy was performed with the aid of depth microrecording. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…The obstacles faced by pathological assessment are related to the risks of an LP analysis, especially traumatic LPs. However, nowadays new techniques are developed that may help minimize the risk, such as stereotactic biopsy (208,209). If this technique would be learned by more specialists, CNS leukemia would be diagnosed faster and more accurate (205).…”
Section: Cns Leukemia-diagnostic Toolsmentioning
confidence: 99%
“…The obstacles faced by pathological assessment are related to the risks of an LP analysis, especially traumatic LPs. However, nowadays new techniques are developed that may help minimize the risk, such as stereotactic biopsy (208,209). If this technique would be learned by more specialists, CNS leukemia would be diagnosed faster and more accurate (205).…”
Section: Cns Leukemia-diagnostic Toolsmentioning
confidence: 99%
“…Accumulating evidence has suggested that stereotactic biopsy of the brainstem and deep brain lesions is accurate, safe, and has a low incidence of complications (5,7,10,(17)(18)(19). At present, however, the brain lesions that can be biopsied based on the imaging characteristics evaluated by neurologists and neurosurgeons are still limited.…”
Section: Discussionmentioning
confidence: 99%
“…One of the disadvantages of the established stereotaxy is deviation during the procedure and its execution at the present time in the MRI or CT preoperative images. Currently, efforts are being made to overcome the problem by real-time MRI-induced biopsy with promising results [10,11]. In certain cases, when we have an extremely small tumor, the precision of biopsy is questionable with disappointing pathohistological results.…”
Section: The Present Challenges and Future Of Biopsymentioning
confidence: 99%
“…In certain cases, when we have an extremely small tumor, the precision of biopsy is questionable with disappointing pathohistological results. Today, microelectrodes are used to do the microrecording of the brain electrical potential on the biopsy path and in the target tumor zone with the absence of electrical potentials, performing biopsy by the "real time" method and increasing safety and precision [10].…”
Section: The Present Challenges and Future Of Biopsymentioning
confidence: 99%